2019
DOI: 10.1002/pi.5833
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel freeze‐dried silanated chitosan bone tissue engineering scaffold reinforced with electrospun hydroxyapatite nanofiber

Abstract: Novel chitosan scaffolds containing different weight ratios of electrospun hydroxyapatite nanofibers (n-HAs) were fabricated. The fibers possessed diameters in the range 110-170 nm. A fixed concentration of glycidyloxypropyl-trimethoxysilane (GPTMS) as a crosslinking agent was added to the chitosan solution (CG). The porosity percentage was increased when GPTMS and n-HAs were added to the chitosan structure. The presence of GPTMS in the chitosan structure caused a decrease in the average pore size. The pores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
(75 reference statements)
1
11
0
Order By: Relevance
“…This range can be termed as the processing window or optimum range beyond which electrospinning is not possible. Many applications of electrospun fibers and membranes include biomedical (tissue engineering [12][13][14], drug delivery [15][16][17], immobilization of enzymes [18][19][20], wound dressing [21][22][23] and antibacterial membranes [24][25][26]), textiles [27][28][29], separation membranes (Li ion battery separators [30][31][32], distillation [33][34][35] and filtration membranes [36][37][38]), sensors [39][40][41], and high performance composite materials (reinforcing agents [42][43][44] or vascular networks of healing agents [45][46][47]), etc.…”
Section: Electrospinning Parameters and Their Influence On Mechanicalmentioning
confidence: 99%
“…This range can be termed as the processing window or optimum range beyond which electrospinning is not possible. Many applications of electrospun fibers and membranes include biomedical (tissue engineering [12][13][14], drug delivery [15][16][17], immobilization of enzymes [18][19][20], wound dressing [21][22][23] and antibacterial membranes [24][25][26]), textiles [27][28][29], separation membranes (Li ion battery separators [30][31][32], distillation [33][34][35] and filtration membranes [36][37][38]), sensors [39][40][41], and high performance composite materials (reinforcing agents [42][43][44] or vascular networks of healing agents [45][46][47]), etc.…”
Section: Electrospinning Parameters and Their Influence On Mechanicalmentioning
confidence: 99%
“…Adapted with permission. [ 108 ] Copyright 2019, John Wiley and Sons; D) gas‐foaming. Adapted with permission.…”
Section: Definitions Methods and Implications Of Materials Porositymentioning
confidence: 99%
“…Adapted with permission. [ 108 ] Copyright 2019, John Wiley and Sons. SEM images also show D) the unique porous structure of ePTFE.…”
Section: Tissue‐specific Applications Of Porous Biomaterialsmentioning
confidence: 99%
“…In recent years, preparing hydroxyapatite-related materials by electrospinning has been widely studied. Many studies have shown that hydroxyapatite can be combined with gelatin [ 247 ], collagen [ 248 ], silk [ 249 ], PCL [ 250 ], chitosan [ 251 ] and so on, making it more suitable for bone repair. For example, Chen et al [ 252 ] prepared gelatin–chitosan core–shell structure nanofibers using coaxial electrospinning technology.…”
Section: Applicationsmentioning
confidence: 99%